Brain Magnetic Spectroscopy Imaging and Hereditary Spastic Paraplegia: A Focused Systematic Review on Current Landmarks and Future Perspectives - Vavla, Marinela; Montanaro, Domenico; Pizzighello, Silvia; Frijia, Francesca; Arrigoni, Filippo; Baratto, Alessandra; Piccoli, Gianluca; Paparella, Gabriella; Martinuzzi, Andrea (Frontiers in Neurology, 2020)
Magnetic Resonance Spectroscopy (MRS) is a non-invasive neuroimaging technique used to investigate in vivo brain metabolites. MRS could provide a sensitive tool for the study of Hereditary Spastic Paraplegia (HSP) by helping to unveil the underlying biochemical mechanisms and monitoring response to treatment. This focused systematic review aimed to summarize the brain metabolite findings in studies performed in genetically-determined HSP. The second aim was to provide a critical analysis and recommendations for well-designed protocols for future studies. Fourteen MRS studies have been analyzed with overall 61 HSP patients, falling within a wide range of age at onset, disease duration and age at the MRS scan, including children and adults. The genetic diagnosis included several subtypes (SPG2/3a/4/5/10/11/28/31/54). SPG11 and SPG54 have been more frequently investigated. The MRS methodology included different MR field strength, not easily comparable spectra areas varying from the whole brain sampling to various cortical areas, brain stem and cerebellum. No consistency in disease severity and other outcome measures was observed. The main MRS findings corresponded to the White Matter metabolites abnormalities in the corticospinal tracts. In summary, this focused review provides insights on the current knowledge of brain metabolites in HSP, and in particular in SPG11 and SPG54. Despite the inhomogeneity of the studies to date reported, brain metabolites as assessed by MRS could represent potentially useful diagnostic markers and prognostic indicators of disease progression in HSP. Specific recommendations regarding the MRS technical protocol, CNS areas sampling, study design and applicability of findings are given.